Coenzyme Q10 Prevents the Interleukin‐1 Beta Induced Inflammatory Response via Inhibition of MAPK Signaling Pathways in Rat Articular Chondrocytes. Issue 8 (17th September 2017) - Li, Xing; Guo, Yuanqing; Huang, Shuai; He, Minhui; Liu, Qiaoli; Chen, Weizhi; Liu, Minghao; Xu, Dongliang; He, Peiheng
ABSTRACT: Preclinical Research Osteoarthritis (OA) is a widely prevalent degenerative joint disease that severely impairs the health of the elderly population resulting in a heavy economic burden worldwide. Coenzyme Q10 (CoQ10) has shown anti‐inflammatory effects in some diseases. The present study aimed to investigate if CoQ10 would suppress catabolic responses of interleukin (IL)‐1β‐induced chondrocytes. Rat chondrocytes were cultured and pretreated with CoQ10, and then stimulated with or without IL‐1β (10 ng/ml). The expression and production of matrix metalloproteinase (MMP)‐3, MMP‐9, and MMP13 were determined using real‐time PCR and Western blotting. CoQ10 suppressed MMP‐3, MMP‐9, and MMP13 production induced by IL‐1β, and markedly inhibited IL‐1β‐induced MAPK pathways in rat chondrocytes. The present study provides insight into potential mechanisms by which CoQ10 protects against degeneration of cartilage in patients with OA, which may lead to new approaches for the treatment of OA.Drug Dev Res 78 : 403‐410, 2017. © 2017 Wiley Periodicals, Inc.